Tracing Paths of Love through Poetic Inquiry - Borhani, Maya T. (Art/Research International)

(untitled) (University of Alberta, 2022)
In response to this call for poetic inquiries that speak the dynamism of an animate pluriverse, that honor what we hold sacred, and that might serve as medicine during these cataclysmic times, these poems-as-research offer a meditation on the power of love in myriad forms, to teach, inspire and sustain us. Weaving mythopoetic thought and imagery amongst everyday events and mundane realities, love surfaces as core currency. Evoking the wonder of children, and the love and care of teachers, mentors, and friends, these poems sing love in the world, and love of the world—the animated natural world, and the written wor(d)ld as expressive animation of what we love. Specifically, this poetic inquiry traces three synchronous veins of love in my life as they weave through my writing-as-research: love for my daughters (and the intractable wonder of childhood); love for a beloved teacher and mentor, American poet Robert Bly; and love as secular-spiritual awakening, the beating heart of social justice and personal/political activism. Tracings of love in our lives, etched and echoed through poetry as inquiry.